Development of upper limb functions and self-assessment in students with cerebral palsy in inclusive education - Lénárt, Zoltán; Osváth, Maja; Hegedüs, Dominika; Szabó-Szemenyei, Eszter (Gyermeknevelés Tudományos Folyóirat, 2022)
Upper limb movements are essential from a very early age in children’s learning processes, and play an important role in school tasks such as handwriting. In cerebral palsy (CP), the functions of upper limbs are often impaired, a factor that affects children’s learning success. The aim of this paper is to briefly present the results of research that has been carried out in recent years at the Eötvös Loránd University’s Bárczi Gusztáv Faculty of Special Needs Education, investigating the upper limb movements of students with CP and their self-assessment of function. Standardized hand function tests (MACS, QUEST, JHFT, Abilhand-Kids specific to CP) were used to assess upper limb function, and the International Classification of Functioning, Disability, and Health core sets for CP (ICF core set for CP) was used to self-assess functioning of students. The results suggest that CP pupils in inclusive education have a high level of upper limb function in general; they do not generally report serious problems with their own function and their environment, but they rate themselves lower than their peers in special education. Changes during the school year were poorly detectable. The ICF-based self-assessment also highlighted problems that other outcome measure methods cannot detect but may affect school life.